2023
DOI: 10.1186/s12917-023-03616-1
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cells modulate infection and inflammation in the uterus and mammary gland

Abstract: The use of mesenchymal stromal cells (MSCs) is emerging as an efficacious and safe treatment for many infectious and non-infectious inflammatory diseases in human and veterinary medicine. Such use could be done to treat mastitis and metritis, which are the most common disease conditions affecting dairy cows leading to considerable economic losses and reduced animal welfare. Currently, both disease conditions are commonly treated using local and systemic administration of antibiotics. However, this strategy has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Prior to that, females were treated with Depo-Provera (Pfizer Inc., New York City, NY, USA), which contains medroxyprogesterone acetate (MPA), for synchronization into diestrus stage. Diestrus stage was chosen according to our previous studies and experience [66]. The MPA (3 mg per mouse) was subcutaneously injected once on day 1 and a second time on day 5.…”
Section: Collection Of Uterine Tissuesmentioning
confidence: 99%
“…Prior to that, females were treated with Depo-Provera (Pfizer Inc., New York City, NY, USA), which contains medroxyprogesterone acetate (MPA), for synchronization into diestrus stage. Diestrus stage was chosen according to our previous studies and experience [66]. The MPA (3 mg per mouse) was subcutaneously injected once on day 1 and a second time on day 5.…”
Section: Collection Of Uterine Tissuesmentioning
confidence: 99%
“…Then MSCs promote the T lymphocytes proliferation and the migration of Th17 cells 9 . The first such experiments concerned the use of fetal bovine MSCs (FBSC) 10 , and more recently, MSCs have also been isolated from adipose tissue 11 and the umbilical cord 12 , 13 . This study describes the effectiveness of an allogeneic suspension of stem cells derived from bone marrow (BMSC) and adipose tissue (ADSC) in the treatment of subclinical udder inflammation in dairy cows.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that E. coli appeared in the uterus within a few days of postpartum cows, followed by C. necrophorum and Cryptobacterium septicum ( Jeon and Galvao, 2018 ). Numerous studies have revealed that E. coli was one of the most important pathogenic bacteria causing postpartum uterine infections in dairy cows ( Ma et al, 2018 ; Schouten et al, 2023 ). Though the random amplification of polymorphic DNA and 16S rRNA gene sequencing of uterine contents and vaginal secretions of dairy cows with puerperal metritis, Wang et al (2013) demonstrated that E. coli was predominant in both uterus and vagina.…”
Section: Introductionmentioning
confidence: 99%